Edible cannabis for chronic low back pain: associations with pain, mood, and intoxication - Melendez, Samantha N.; Ortiz Torres, Marco; Lisano, Jonathan K.; Giordano, Gregory; Skrzynski, Carillon; Hutchison, Kent E.; Bryan, Angela D.; Bidwell, L. Cinnamon (Frontiers in Pharmacology, 2024)
Cannabis, commonly known for both therapeutic and intoxicating effects, is gaining accessibility on legal markets and traction as a potential alternative therapy for pain mediation, particularly in those suffering from chronic low back pain. However, the effectiveness in this population of legal market forms of cannabis, particularly commonly used edibles, is unknown. Therefore, this study utilized a naturalistic prospective design where participants with chronic low back pain with intentions to initiate cannabis use for treatment were recruited and self-selected edible cannabis products containing varying amounts of delta-9 tetrahydrocannabinol (THC) and cannabidiol (CBD). Products were categorized as CBD-dominant, THC-dominant, or combined THC and CBD (THC + CBD). 249 participants (140 female [56.62%], mean (SD) age of 46.30 [16.02], 90% White) were tracked over two weeks of ad libitum use and assessed during a naturalistic acute cannabis administration session on changes in pain, mood, and subjective drug effects. During acute administration, a significant correlation between THC dose and short-term pain relief was found, suggesting that higher THC doses were associated with greater pain reduction (p<.05). In addition, THC was associated with higher levels of subjective cannabis drug effects (p<.001), regardless of whether CBD was also in the edible product. Acute CBD dose was primarily associated with short-term tension relief (p<.05); however, there were no associations between CBD dose and acute pain. Over the 2-week ad libitum administration period results suggested pain reductions across participants using all forms of cannabis. However, trends suggested that more frequent use of CBD-dominant edible cannabis may be associated with greater reductions in perceived pain over the two-week observation period (p=.07). These findings support the short-term analgesic effects of THC and anxiolytic effects of CBD and further suggest that orally-administered THC and CBD should continue to be evaluated for the potential to provide both acute and extended relief from chronic low back pain.